Progressive pulmonary fibrosis during a pandemic: assessment of risk factors and modern approaches to treatment - Elena N. Popova; Andrei B. Ponomarev (LLC "MEDIAFORMAT", 2021)
Complex of medicine that increases the body's resistance to the damaging effects of viruses during a pandemic in the long term will be an important tool not only to reduce the overall incidence of diseases, but also to improve the prognosis of those who have been ill due to the reduction of residual fibrotic changes in the lungs.